A 115-Year-Old Woman: The Oldest Individual in Japan - Ojika, Kosei; Inagaki, Aki; Yamamoto, Toshiyuki; Niimi, Tatsuji; Hashizume, Yoshio; Inagaki, Toshiaki; Mizuno, Tomoyuki (Nihon Rōnen Igakkai zasshi, 1995)
The purpose of this study was to assess the back-ground to the longevity of a 115-year-old woman who was the oldest individual in Japan as of September, 1994. The secrets of her social and medical profile appeared to be hereditary factors, well-balanced meals, no smoking or drinking, sufficient sleep and adequate exercise. From the viewpoints of psychological aspects and comprehensive functional assessment of the elderly, she clearly has a tenacious personality. Furthermore, she has maintained independence in her activities of daily living, and did not suffer from senile dementia until 107 years of age. From the medical standpoint, she has suffered from transient hypertension, but her left ventricle function has remained within the normal echocardiography range and no greatly abnormal values have been observed in blood chemistry tests. She has suffered from pneumonia and urinary tract infection many times since the age of 109, and on these occasions she was promptly admitted to our hospital and received appropriate medical treatment. We consider that this also played an important role in her longevity.